Czas wolny polaków z perspektywy zmian społeczno-ustrojowych: od ogniska do barbecue = The Poles` leisure time from the viewpoint of social and political changes: from a bonfire to a barbecue - Trzop, Beata (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents changes that have occurred in the past 20 years in the field of leisure time of the Poles. Both the issue of changes in the very amount of free time as well as the ways of spending it by representatives of different social categories appear interesting. The article contains existing data illustrating various ways of spending leisure time, i.e., active (e.g., sports, family and friends meetings) and passive (e.g., watching TV, browsing the Internet) both before the transformation period and within the last 20 years.
Keywords: czas wolny; Polacy; transformacja ustrojowa; zmiana